A Mixed Methods Empirical Examination of Changes in Emphasis and Style in the Extremist Magazines Dabiq and Rumiyah - Wignell, Peter; Tan, Sabine; O'Halloran, Kay; Lange, R. (University of Massachusetts Lowell, 2017)
The change in name of ISIS’s flagship English language magazine from Dabiq to Rumiyah prompted media speculation about its significance. This article uses a mixed methods approach that integrates a qualitative social semiotic discourse analysis approach with quantitative methods of information visualisation to examine empirically changes in emphasis and approach in both magazines over time to determine whether the changes are ones of style or substance. The paper argues that, while ISIS has changed its strategic focus over time in response to its changing fortunes, the organisation’s underlying world view, values and ultimate aims remain consistent and unchanged.